Estudo da liberação controlada de sinvastatina utilizando nanofibras de PLA/PEG produzidas por fiação por sopro em solução - Ferreira, Kaline do Nascimento (2017)
Preparation and characterization of poly(lactic acid) (PLA) and Poly (ethylene glycol) (PEG) nanofibers for controlled release applications containing simvastatin (SIM) produced by Solution Blow Spinning (SBS) were investigated. Nanofibers with PLA/PEG ratios of 9: 1, 8: 2 and 7: 3), with the incorporation of 2.5, 5.0 and 7.5 % simvastatin were prepared from chloroform (15% w/v). In this study, a 24 + 3 experimental design was used to optimize the processing parameters. Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), thermogravimetry (TGA), X-Ray diffractometry (XRD) and contact angle measurements were used to characterize the produced nanofibers and the morphology was investigated by scanning electron microscopy (SEM). The release of SIM from these new drug delivery systems was followed by UV–VIS spectroscopy. SEM analysis revealed that small diameter fibers were best obtained by a combination of concentration of SIM versus gas pressure. FTIR results indicated the successful incorporation of SIM into the fibers. Also, the SBS processes increased the PLA crystallinity and with the addition of PEG. Nanofibers with higher PEG incorporations presented lower thermal stabilities, associated to a reduction in diameter, providing a greater surface area, as well as, showing greater water sorption values due to the hydrophilic nature of PEG. In addition, the physicochemical interaction between polymers and drug resulted in total fiber wettability. Release kinetics of SIM presented a homogeneous profile with a rapid initial release, followed by slow release up to 21 days, with a more pronounced release kinetics with increasing PEG content in the blends (7: 3). The drug incorporation and physicochemical characterisation data obtained in this study may be relevant in optimising the drug incorporation and delivery properties of these potential drug targeting carriers.